Usefulness of two‐ and three‐dimensional transesophageal echocardiography in combined mitral valve‐in‐valve implantation and paraprosthetic leak closure. Issue 4 (23rd March 2018) - Ahmed, Mustafa I.; Arisha, Mohammed J.; Nanda, Navin C.; Lewis, Clifton T. P.; Eudailey, Kyle W.
Abstract : We demonstrate the usefulness of two‐ and live/real time three‐dimensional transesophageal echocardiography in a procedure, which combined transcatheter mitral valve‐in‐valve deployment and paraprosthetic leak closure in the same setting using the less invasive transfemoral approach in an adult patient with bioprosthetic mitral valve degeneration. We also highlight the additive value of three‐dimensional echocardiography over the two‐dimensional technique.